Answer:
Step-by-step Simplifying
6 + -3x = 4 + -1x + -3 + -2x
Reorder the terms:
6 + -3x = 4 + -3 + -1x + -2x
Combine like terms: 4 + -3 = 1
6 + -3x = 1 + -1x + -2x
Combine like terms: -1x + -2x = -3x
6 + -3x = 1 + -3x
Add '3x' to each side of the equation.
6 + -3x + 3x = 1 + -3x + 3x
Combine like terms: -3x + 3x = 0
6 + 0 = 1 + -3x + 3x
6 = 1 + -3x + 3x
Combine like terms: -3x + 3x = 0
6 = 1 + 0
6 = 1
Solving
6 = 1
Couldn't find a variable to solve for.
This equation is invalid, the left and right sides are not equal, therefore there is no solution.
Answer:Least common multiple ( LCM ) of 6 and 12 is 12. LCM(6,12) = 12. Least common multiple or lowest common denominator (lcd) can be calculated in two way; with the LCM formula calculation of greatest common factor (GCF), or multiplying the prime factors with the highest exponent factor.
Step-by-step explanation:
Answer:
x=1
y=2
Step-by-step explanation:
Multiply the second equation by 2
and then solve!
Answer:
-3y/5
Step-by-step explanation:
3/5y+(-6/5y)=
Since the denominator is the same, we can add the numerators
3y - 6y
----------------
5
-3y/5
68 students* (25/100)= 17 students.
There are 17 students who had perfect attendance for the nine weeks~